Effects of coke oven emissions and benzo[a]pyrene on blood pressure and electrocardiogram in coke oven workers - Yang, Kai; Jiang, Xuejun; Cheng, Shuqun; Chen, Chengzhi; Cao, Xianqing; Tu, Baijie (Journal of Occupational Health, 2017)
[Abstract] : [Objective] : To evaluate the effects of occupational exposures to coke oven emissions (COEs) and benzo[a]pyrene (B[a]P) on the prevalence of hypertension and abnormal electrocardiogram (ECG) in coke oven workers. [Methods] : We included 880 coke oven workers and 710 oxygen employees in the exposed and control groups, respectively. Blood pressure (BP), ECG, blood lipid levels, and glucose levels of all subjects were measured. COE and B[a]P concentrations at the bottom, side, and top of the oven and control plants were estimated by weighing and high-performance liquid chromatography. [Results] : The COE concentration at the top and side was higher than that at the bottom (P < 0.05). The levels of B[a]P at the top and side significantly exceeded the limit value. Abnormal BP, ECG, the detection ratio of hypertension and left ventricular high voltage were significantly greater in the exposed group than in the control group (P < 0.05). The logistic regression analysis results revealed that age and B[a]P exposure were risk factors for hypertension in coke oven workers (P < 0.05) and both were risk factors for abnormal ECG (P < 0.05). Moreover, B[a]P exposure, age, and gender were risk factors for impaired fasting glucose in coke oven workers (P < 0.05). [Conclusions] : B[a]P and COE exposures are risk factors for hypertension and abnormal ECG in coke oven workers.